178k views
19 votes
Solve the system using elimination.

Solve the system using elimination.-example-1
User Spyros K
by
6.3k points

2 Answers

10 votes

Answer:

(-1, 3)

Explanation:

x - 5y = -16 [Equation 1]

-x + 3y = 10 [Equation 2]

Adding both equations

  • x - x - 5y + 3y = -16 + 10
  • -2y = -6
  • y = 3
  • x - 5(3) = -16
  • x - 15 = -16
  • x = -1

Solution : (-1, 3)

User StandDuPp
by
5.6k points
6 votes

Solving for x and y,

→ (x - 5y = -16) + (-x + 3y = 10)

→ x - 5y - x +3y = -16 + 10

→ -2y = -6

→ y = -6/-2

→ [ y = 3 ]

Finding the value of x,

→ x - 5y = -16

→ x - 5(3) = -16

→ x - 15 = -16

→ x = -16 + 15

→ [ x = -1]

___________________

→ -x + 3y = 10

→ -x + 3(3) = 10

→ -x + 9 = 10

→ -x = 10 - 9

→ [ x = -1 ]

Arranging them in ordered pair,

→ (x,y)

→ (-1,3)

Thus, the solution is (-1,3).

User Lukasz Cwik
by
5.8k points